FID-calibrated simultaneous multi-slice fast spin echo with long trains of hard pulses. (7th February 2022) - Lim, Eun Ji; Sohn, Chul-Ho; Shin, Taehoon; Park, Jaeseok
Abstract: Objective . To develop a novel, free-induction-decay (FID)-calibrated single-shot simultaneous multi-slice fast spin echo (SMS-FSE) with very long hard pulse trains for high encoding efficiency and low energy deposition. Approach . The proposed single-shot SMS-FSE employs a mixed pulse configuration in which a long excitation pulse that is spatially multi-band (MB) selective is used in conjunction with short spatially nonselective refocusing pulses. To alleviate energy deposition to tissues while reducing signal modulation along the echo train, variable low flip angles with signal prescription are utilized in the refocusing pulse train. A time-efficient FID calibration and correction method is introduced before aliased voxels in the slice direction are resolved. Simulations and experiments are performed to demonstrate the feasibility of the proposed method as an alternative to conventional HASTE for generating T 2 -weighted images. Main results . Compared with conventional HASTE, the proposed method enhances imaging speed effectively by an MB factor up to 5 without apparent loss of image contrast while successfully eliminating FID artifacts. Significance . We successfully demonstrated the feasibility of the proposed method as an encoding- and energy-efficient alternative to conventional HASTE for generation of T 2 -weighted contrast.